Evaluation of left ventricular false tendons in children with idiopathic left ventricular tachycardia. Issue 9 (31st July 2018) - Merlocco, Anthony; Brown, David W.; Gauvreau, Kimberlee; Mah, Douglas Y.; Triedman, John K.; Alexander, Mark E.; Walsh, Edward P.
Abstract: Background: Left ventricular false tendons (FT) traverse the ventricular cavity and are thought to have some association with idiopathic left ventricular tachycardia (ILVT). However, reported prevalence of FT varies widely, making correlation difficult. Superior echocardiographic windows of pediatric patients may permit better analysis of FT in ILVT. Our study describes the relationship between FT and ILVT in young patients. Methods: Retrospective case‐control study of 30 ILVT patients with 98 controls compared for FT. Diagnosis of ILVT was made by electrocardiogram and clinical history, and for 25 patients was further confirmed by electrophysiology study (EPS). Presence of FT was identified by one blinded observer and verified by a second blinded observer. Presence of FT was then compared between ILVT patients and controls using Fisher's exact test. Results: Presence of FT did not differ significantly between patients and controls (53% vs 43%, P  =  0.40). Twelve FT patients (19%) had multiple FTs detected, though the incidence of ILVT was no higher in the setting of multiple FTs. A total of 25 patients with ILVT underwent EPS for intended ablation therapy, with ultimate success in 22/25 (88%) after one or more ablation sessions. Of the 25 EPS patients, FTs were present in 11, but precise correlation between successful ablation location and FT location was not possible since intraprocedural echocardiography was not performed in this patient group. Conclusions: Presence of FTs did not differ between ILVT patients and controls. While FTs are not absolutely required for ILVT, they may still play a role in some cases.